Development and Validation of a Reversed-phase HPLC Method for Assay of the Decapeptide Cetrorelix Acetate in Bulk and Pharmaceutical Dosage Forms - Hooshfar, Shirin (Shaheed Beheshti University of Medical Sciences, 2014)
A gradient reversed-phase high performance liquid chromatography (HPLC) method was developed for the assay of cetrorelix acetate, a synthetic decapeptide with gonadotropin-releasing hormone (GnRH) antagonistic activity used in infertility treatment. The HPLC method, which is used to determine cetrorelix in bulk and pharmaceutical dosage forms, was validated per ICH guidelines. The chromatographic separation was achieved on a C18 reversed-phase column using acetonitrile, water and trifluoroacetic acid (TFA) as mobile phase and wavelength was set at 275 nm. The calibration curve was linear (r2 = 0.999) over cetrorelix concentrations ranging from 62.50 to 12.50 μg/mL (n = 6). The limits of detection (LOD) and quantification (LOQ) were calculated from the peak-to-noise ratio as 15.6 and 62.5 μg/mL, respectively. The method had an accuracy of > 97% and intra- and inter-day RSD of < 0.3% and < 1.6%, respectively and was validated with excellent specificity, sensitivity, and stability. The validated method was successfully applied for determination of cetrorelix in bulk and pharmaceutical dosage forms.